2002
DOI: 10.1021/om011040u
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Metal−Carbon Bond versus Metal Reduction during Ethylene Polymerization Promoted by a Vanadium Complex:  The Role of the Aluminum Cocatalyst

Abstract: The dinuclear and trivalent complex {[(Me 3 Si)NCH 2 CH 2 ] 2 N(Me 3 Si)} 2 V 2 (µ-Cl) 2 (1) is the precursor to mono-and dinuclear alkyl derivatives that are thermally stable. For example, treatment with MeLi gives a stable methyl derivative, probably isostructural with 1, which upon further treatment with pyridine affords the mononuclear complex {[(Me 3 Si)NCH 2 -CH 2 ] 2 N(Me 3 Si)}V(CH 3 )(pyridine) (2). However, reaction of 1 with Me 2 AlCl, AlMe 3 , or PMAO-IP yields the tetrametallic species { 3), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Studies of the oxidation state of vanadium catalysts for ethylene polymerization have generally revealed that V(III) and V(IV) precursors are often reduced to inactive V(II) species [9][10][11][12]. Alkyl vanadium(III) complexes bearing amidinate [13,14] and amide [15,16] ligands produce shortlived ethylene polymerization catalysts and are inactive in propene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the oxidation state of vanadium catalysts for ethylene polymerization have generally revealed that V(III) and V(IV) precursors are often reduced to inactive V(II) species [9][10][11][12]. Alkyl vanadium(III) complexes bearing amidinate [13,14] and amide [15,16] ligands produce shortlived ethylene polymerization catalysts and are inactive in propene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the above reports (vanadium complexes using chelate anionic and neutral donor ligands) [91][92][93][94][95][96][97][98], as described above, control, stabilization of the oxidation state, catalytically active species) by an appropriate ligand modification seems to be a key for the efficient catalyst with vanadium(III), …”
Section: Vanadium(iii) (Iv) Complexesmentioning
confidence: 91%
“…The reaction of 19 with AlCl 3 afforded disproportionated compounds, (tetravalent) 19c and (one divalent and two trivalent) 19d, clearly indicating that disproportionation was the basis of a reduction of the vanadium center. These results suggested a possibility of the reduction of 19 affording 19b and that the addition intermediate 19a, which is likely to be the catalytically-active species, has the intrinsic instability of a vanadium-carbon bond [91].…”
Section: Vanadium(iii) (Iv) Complexesmentioning
confidence: 93%
See 1 more Smart Citation
“…The compound 47 with M = Zr and D = N could be activated by B(C 6 F 5 ) 3 for ethylene and propylene polymerization [132] but the compound 47 with M = V and D = N required Me 2 AlCl for ethylene polymerization [140].…”
Section: Tridentate Diamide Ligandsmentioning
confidence: 99%